Trends in the Occurrence of Compound Extremes of Temperature and Precipitation in Côte d’Ivoire - Elisée Yapo Akobé; Adama Diawara; Fidèle Yoroba; Benjamin K. Kouassi; Assi Louis Martial Yapo; Ibrahima Diba; Kouakou Kouadio; Dro T. Tiémoko; Dianikoura Ibrahim Koné; Arona Diedhiou (Atmosphere)
The aim of this study is to characterize the compound extremes of rainfall and temperature in Côte d’Ivoire. For this purpose, we analyzed the outputs of fourteen (14) climate models from the CORDEX-Africa project. Results show an increase (approximately 4.3 °C) in the surface temperature and a decrease (5.90%) of the mean rainfall in the near (2036–2065) and far futures (2071–2100) over Côte d’Ivoire during the January–February–March (JFM) period. The analysis of the compound extremes of the wet/warm type highlights an increase in the frequency of this climatic hazard in the northern and central parts of the country during the January–March (JFM) season in the near and far futures. The dry/warm mode will increase in the central and southern parts of the country in the near future and in the whole country in the far future. These increases in compound extremes could lead to an increase in droughts and natural disasters across the country and could have a negative impact on socio-economic activities, such as transportation and agricultural production. This work could provide decision support for political decision-makers in formulating future public policies for managing agricultural production, food security, and natural disasters.